The Child Maintenance Rights of Orphans from the Perspective of Islamic Law and Positive Law - Hasman Zhafiri Muhammad; Lisa Purwatiningsih; Nashih Muhammad; Mahdee Maduerawae (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2025)
Fulfilling a child’s right to maintenance constitutes both a legal and moral obligation of parents, as stipulated in Indonesian law and Islamic legal principles. Nevertheless, empirical realities reveal persistent neglect of children by biological fathers, particularly in terms of financial and emotional support. This study examines a case from Kebonagung Village, Tegalrejo District, Magelang Regency, in which a child was deprived of maintenance and legal recognition for more than two decades despite the absence of a legally dissolved marriage. This condition exposes a significant gap between normative legal provisions and their practical enforcement, underscoring structural weaknesses in the protection of children’s rights within the domestic sphere. As a consequence, such children occupy a vulnerable legal position and may be classified as “passive orphans,” referring to children whose parents are legally alive but fail to fulfill their maintenance obligations. This article argues for the urgency of strengthening legal protection mechanisms and enhancing the role of the state in ensuring the effective realization of children’s non-negotiable right